2022
DOI: 10.3390/insects13070580
|View full text |Cite
|
Sign up to set email alerts
|

To Every Thing There Is a Season: Phenology and Photoperiodic Control of Seasonal Development in the Invasive Caucasian Population of the Brown Marmorated Stink Bug, Halyomorpha halys (Hemiptera: Heteroptera: Pentatomidae)

Abstract: Studies on the phenology of local populations of invasive insects are necessary for monitoring and predicting their dispersion. We investigated the phenology of the brown marmorated stink bug, Halyomorpha halys, in the Sochi region (Krasnodar Territory, Russia) from 2018 to 2021 by regular field sampling and dissecting. The results of the sampling suggest that H. halys is at least partially bivoltine in the studied region: the main period of mass oviposition (by the overwintered females) occurs from June to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Subsequently, this delays the appearance of summer generation adults, which begin to reproduce when the photoperiod is already decreasing. Our observations could be well explained by research of Reznik et al [ 41 ], who found that with decreasing photoperiod (<15.0–15.5 h), the proportion of females with fully developed ovaries is drastically reduced. Contrastingly, increasing photoperiod is closely related to increased reproductive output [ 45 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Subsequently, this delays the appearance of summer generation adults, which begin to reproduce when the photoperiod is already decreasing. Our observations could be well explained by research of Reznik et al [ 41 ], who found that with decreasing photoperiod (<15.0–15.5 h), the proportion of females with fully developed ovaries is drastically reduced. Contrastingly, increasing photoperiod is closely related to increased reproductive output [ 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…As H. halys is a recently established invasive pest in Europe, there is still a lack of basic biological knowledge in the newly invaded areas, which is essential for the development of management solutions. Three studies of H. halys biology have been carried out in Europe so far, namely Swiss research that reported the existence of one generation/year in the area of Zurich [ 29 ], an Italian study showing that south of the Alps H. halys develops two generations/year [ 30 ] and Russian one which confirmed bivoltinism of the species in Sochi region [ 41 ]. The basic findings of our research are in line with the results of Italian study.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that females require some additional time to terminate diapause once they leave their overwintering sites. In recent works, Nielsen et al [ 25 ] and Reznik et al [ 10 ] also concluded that H. halys enters reproductive diapause in temperate locations in the fall and that a delay occurs in developmental maturity after diapause termination in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…It overwinters as an adult and produces offspring in the midsummer, when most of the feeding damage occurs [ 8 ]. In the mid-Atlantic US states and Russia, it is considered bivoltine [ 9 , 10 ], and adults overwinter in concealed, sheltered locations, underneath bark of trees or human-made structures [ 11 ], within which thousands of individuals cluster together [ 12 ]. In these regions, H. halys adults begin to emerge from overwintering sites in April [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adult bugs seeking winter shelter often climb into houses, causing discomfort to humans [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. It is known that in its both native and invasive ranges H. halys overwinters in the state of adult (reproductive) diapause induced by the long-day type photoperiodic response [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. It was shown that the critical photoperiod (that is the day length, which induces diapause in 50% of the population) of individuals from the native Korean population significantly differs from that of the bugs from different invasive European populations [ 33 ].…”
Section: Introductionmentioning
confidence: 99%